Promoting regional trade in the SADC region: identifying opportunities for manufactured exports from South Africa to Botswana, Mozambique, Namibia, Zambia and Zimbabwe - Moodliar, Loshini (Research of GSB, 2018)
The purpose of this study is to, firstly, identify opportunities for manufactured exports from South Africa to its five largest trading partners in the SADC region, namely Botswana, Mozambique, Namibia, Zambia and Zimbabwe. Secondly, the study investigates the challenges facing South African firms in exporting to the SADC markets and the strategies that can be pursued to overcome these challenges. The study uses a mixed-methods approach where secondary quantitative data was analysed to identify manufactured products with high potential for export to the selected SADC countries. Semi-structured interviews were used to answer the secondary research questions related to identifying export challenges facing South Africa, and strategies to overcome these challenges. It was found that the products with the highest potential for export to the five countries are mainly found in heavy duty vehicles, automobiles, pharmaceuticals, structural and building materials, construction machinery and equipment, and petroleum oils and other petroleum products. The main challenges, as well as strategies to overcome these challenges, were grouped into seven themes as follows: Facilitation of Trade; Understanding the SADC Market; South Africa's relationship with the Rest of Africa; Non-tariff Barriers; Regional Integration; South African competitiveness; and Competition. The recommendations of the study include South Africa developing a more tailored approach to doing business with the SADC countries in terms of product and service offerings as well as trade promotion activities. Furthermore the development of a market intelligence database, training programmes, a cohesive marketing strategy for the country's capabilities and a regional value chain approach are recommended. It is hoped that the findings of the study will contribute towards informing the development of a targeted regional export strategy for South Africa.